GIS-material for the archaeological project: Stone settings and a Stone Age shore - House construction by Kallerstad 1:27 - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to planned house construction within the property Kallerstad 1:27, in the city and municipality of Linköping, Östergötland County, the Swedish National Heritage Board's Contract Archaeology Service, UV Öst, performed a field evaluation in October-November 2004. In connection with previous surveying in the area, several archaeological remnants, such as graves, settlement remains and worked quartz, were discovered. Trial trenches were dug during the evaluation, exposing at least six separate stone packings. The highest point in the area contains a burial ground with stone settings, preliminarily dated to the early Iron Age. East of the burial ground is an area with hearths, most likely linked to the graves. The hearths overlie a Mesolithic settlement. UV Öst suggests that parts of the evaluation area to be excavated prior to further development.

Purpose:

The information in the purpose is translated from the archaeological report:
The aim of the field evaluation was to determine the dating, type, intensity and extent of the archaeological remains. Three themes were formulated (The burial environment, The settlement environment and The Stone Age Settlement). The general aim was to find the spacial and chronological relations between the various prehistoric activities in the area.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Linköpings Mäklarbyrå planerar att uppföra hus och villor inom fastigheten Kallerstad 1:27 i Linköping stad och kommun, Östergötland. Vid en tidigare utredning i området kunde konstateras ett flertal fornlämningar i form av gravar, boplatslämningar samt bearbetad kvarts, vilka anmäldes som fornlämning. Efter beslut av Länsstyrelsen i Östergötland utförde Riksantikvarieämbetet, UV Öst, under oktober och november 2004 en arkeologisk förundersökning i det berörda området.
Vid förundersökningen togs sökschakt upp inom fornlämningsområdet. Minst sex separata stenpackningar kunder dokumenteras. Krönrygget i området utgörs av ett gravfält med stensättningar, preliminärt daterat till äldre järnålder. Öster om gravfältet ligger ett härdområde som sannolikt kan knytas till gravarna. Dessa härdar överlagrar en bosättning som typologiskt kan dateras till senmesolitikum. Riksantikvarieämbetet, UV Öst, föreslår att delar av området blir föremål för slutundersökning vid en eventuell fortsatt exploatering.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med förundersökningen var att klargöra datering, art och intensitet av lämningarna samt att ytterligare begränsa fornlämningarnas utbredning. Tre tematiska delar urskildes (Gravmiljön, Boplatsmiljön, Stenåldersbosättningen) och en övergripande målsättning var att försöka finna de rumsliga och kronologiska relationerna mellan de olika förhistoriska aktiviteterna i området.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Stensättningar och stenåldersstrand - Husbygge vid Kallerstad 1:27
Keywords: stone age; stenålder; Bronze Age; bronsålder; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi